A comprehensive picture on chain walking olefin polymerization. (16th January 2023) - Zhang, Yuxing; Zhang, Yixin; Jian, Zhongbao
Abstract: α-Diimine nickel and palladium catalyzed α-olefin polymerization could produce polyolefins with complicated branching structures due to the chain walking feature. The thorough understanding of the polymer microstructure could provide a general picture of monomer enchainment including the insertion selectivity and chain walking pathways. By utilizing α-diimine nickel (DBB-Ipty-Ni ) and palladium (DBB-Ipty-Pd ) catalysts reported previously by us that show an excellent selectivity in ethylene polymerization, homopolymerizations of linear α-olefin such as 1-pentene, 1-hexene and 1-octene, and non-linear α-olefin 4-methyl-1-pentene (4M1P) were conducted. In-depth studies of the polyolefin microstructures revealed the enchainment of α-olefin monomers, in which the enchainment of 4M1P indicated a chain-end control on the insertion regio-selectivity. Moreover, internal olefins including cis -2-hexene and cis -3-hexene, and non-conjugated diolefin 1, 7-octadiene were successfully polymerized by the α-diimine palladium catalyst. It is worth noting that the isomerization of internal olefins to 1-alkenes in polymerization was found. Chain walking cyclopolymerization of 1, 7-octadiene occurred to produce an alternating cyclic copolymer bearing cis -five- and cis -six-membered rings on the polymer backbone. A rational enchainment mechanism was proposed to explain the formation of the special alternating cyclic chain structure. In addition, mechanical properties of poly(α-olefin)s were studied, among which poly(1-octene) exhibited the highest tensile stress-at-break (17.9 MPa) and strain-at-break (1480%), while poly(1-pentene) showed the best strain recovery (81%). Graphical abstract: Image 1 Highlights: Studies on microstructures of polyolefins enable a comprehensive understanding of chain walking olefin polymerization. Chain-end control exists in chain walking polymerization of non-linear alfa-olefin. Isomerization occurs in chain walking polymerization of internal olefin. Alternating five- and six-membered cyclic structure is observed in chain walking polymerization of non-conjugated diolefin.